Total Extracts of Abelmoschus manihot L. Attenuates Adriamycin-Induced Renal Tubule Injury via Suppression of ROS-ERK1/2-Mediated NLRP3 Inflammasome Activation - Li, Wei; He, Weiming; Xia, Ping; Sun, Wei; Shi, Ming; Zhou, Yao; Zhu, Weiwei; Zhang, Lu; Liu, Buhui; Zhu, Jingjing; Zhu, Yiye; Zhou, Enchao; et al. (Frontiers in Pharmacology, 2019)
Abelmoschus manihot (L.) Medik. (Malvaceae) is an herb used in traditional Chinese medicine to treat some kidney diseases. To date, the detailed mechanisms by which A. manihot L. improves some kinds of renal disease are not fully understood. In this study, we established Adriamycin-induced NRK-52E cells, the normal rat kidney epithelial cell line, and Sprague-Dawley rats with Adriamycin-induced nephropathy to evaluate the role and mechanisms of total extracts of A. manihot L. flower (TEA) both in vitro and in vivo. We found that TEA ameliorated Adriamycin-induced cellular morphological changes, cell viability, and apoptosis through the suppression of protein oxidation and ERK1/2 signaling. However, this anti-oxidative stress role of TEA was independent of ROS inhibition. Adriamycin activated ERK1/2 signaling followed by activation of NLRP3 inflammasomes. TEA suppressed NLRP3 inflammasomes via inhibition of ERK1/2 signal transduction; decreased proteinuria and attenuated renal tubule lesions; and inhibited the expression of NLRP3 in tubules in rats with Adriamycin nephropathy. Collectively, TEA protects renal tubular cells against Adriamycin-induced tubule injury via inhibition of ROS-ERK1/2-NLRP3 inflammasomes.